Comparative X-ray photoelectron spectroscopy analysis of nitrogen atoms implanted in graphite and diamond - Auciello, Orlando; Veyan, Jean-François; Arellano-Jimenez, Maria J. (Frontiers in Carbon, 2023)
Insertion of N atoms at nanoscale sub-surface depth in single crystal diamond (SCD) may enable new generations of quantum electronics devices. In this sense, it is critical to understand the interaction between implanted N atoms and C atoms in the diamond lattice. The investigation of N atoms interaction with SCD at the atomic scale using X-Ray Photoelectron Spectroscopy (XPS) analysis, involves in-situ bombardment of the SCD surface with relatively low energy (5,000 eV) N2+ ions. In Situ XPS analysis of SCD and Highly Oriented Pyrolytic Graphite (HOPG), before/after N atoms implantation, are compared with published XPS analysis of C-N materials (e.g., g-CN, N in poly/single crystal diamond). They revealed three N1s peaks at 398-399 eV (N1), 399-400.5 eV (N2) and 401-403 eV (N3), with N1/N2 peaks assigned to C-N bonds and N3 peak inaccurately assigned, in prior publications, to N-bonded contaminants (e.g., O, NH). In situ cleaning of the SCD and HOPG surfaces prior to N atoms implantation, were performed to eliminate all atmospheric contaminants. This cleaning process revealed that the N3 peak is associated to N-C bonded atoms and not C- O/NH linkage, as previously suggested. Ex situ HRTEM studies of N-implanted SCD shows defect-structured subsurface region. An important side effect of the relatively low energy N implantation in SCD is the formation of a 5-8 nm electrically conductive surface layer, an effect that may open the pathways for future research in diamond-based micro-/nano-electronics.